Variation in cork production of the cork oak between two consecutive cork harvests - Costa, A.; Oliveira, A. C. (Forestry, 2001)
The variation in the cork produced by individual trees (Quercus suber L.) in three distinct locations, Mora, Alcácer do Sal and Benavente, is characterized by measurements made during two consecutive harvests of cork in the same trees. Particular emphasis is given to the variability in the weight of cork produced by individual trees and its mean caliper for the two strippings in each region. A good linear correlation between the tree circumference after the first stripping and the weight of the cork produced 9 years later as well as a poor linear correlation between the first variable and the caliper of the cork produced 9 years later is reported. A cork oak diameter curve is presented for each region, considering their two radial growths: the wood growth, which is cumulative, and the cork growth, which is the 9‐year growth.
10.1093/forestry/74.4.33710.1093/forestry/74.4.337
Keywords: Cork Production; Growth (PG); stripping; variability

Variation in cork production of the cork oak between two consecutive cork harvests - Costa, a; Oliveira, A C (Forestry, 2001)
The variation in the cork produced by individual trees (Quercus suber L.) in three distinct locations, Mora, Alcácer do Sal and Benavente, is characterized by measurements made during two consecutive harvests of cork in the same trees. Particular emphasis is given to the variability in the weight of cork produced by individual trees and its mean caliper for the two strippings in each region. A good linear correlation between the tree circumference after the first stripping and the weight of the cork produced 9 years later as well as a poor linear correlation between the first variable and the caliper of the cork produced 9 years later is reported. A cork oak diameter curve is presented for each region, considering their two radial growths: the wood growth, which is cumulative, and the cork growth, which is the 9‐year growth.
10.1093/forestry/74.4.337
Keywords: Cork Production; Growth (PG); stripping; variability